2012
DOI: 10.1016/j.clindermatol.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Epidermolysis bullosa acquisita

Abstract: EBA is a rare, acquired, chronic subepidermal bullous disease of the skin and mucosa characterized by autoantibodies to type VII collagen structures, a major component of anchoring fibrils, that attach the epidermis onto the dermis. EBA patients have tissue-bound as well as circulating anti-type VII collagen autoantibodies that attack type VII collagen and result in a reduction or perturbation of normally functioning anchoring fibrils. Patients with EBA have skin fragility, blisters, erosions, scars, milia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
1
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 100 publications
1
114
1
14
Order By: Relevance
“…Detailed characterization of this model showed that it predominantly reflects the inflammatory variant of the human disease (40). Compared with the previous model of immunization-induced EBA (20), immunization with vWFA2 fused to intein leads to both autoantibody production and skin blistering independent of the GST tag.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed characterization of this model showed that it predominantly reflects the inflammatory variant of the human disease (40). Compared with the previous model of immunization-induced EBA (20), immunization with vWFA2 fused to intein leads to both autoantibody production and skin blistering independent of the GST tag.…”
Section: Discussionmentioning
confidence: 99%
“…After binding to their target Ag in the skin, a proinflammatory milieu is generated, leading to both neutrophil extravasation and activation. Reactive oxygen species and proteolytic enzymes released from neutrophils then lead to subepidermal blister formation (29)(30)(31).…”
mentioning
confidence: 99%
“…It is associated with autoantibodies to the N-terminal non-collagenous domain (NC1) of type VII collagen that is the major component of anchoring fibrils in the basement membrane. It has similarities to dystrophic epidermolysis bullosa in which there is a hereditary defect in the gene that encodes type VII collagen, and to BP, although the degree of associated inflammation is more variable, and may be less than that seen in BP [113].…”
Section: The Pemphigoid Syndromesmentioning
confidence: 99%